Potensi Agrowisata Desa Bojong serta Pengembangan Kelapa Kupas - Visnhu, Bartolomeus Galih (Jurnal Atma Inovasia, 2022)
Bojong village has superior coconut varieties which are native to this village, namely Bojong Bulat coconut. The fact that Bojong village is located near the coast certainly affects the level of demand for young coconuts. The large number of coconut trees in this Bojong village makes it possible to make this village an agro-tourism village. Coconuts in Bojong Village can also be used as Peeled Coconut. This study aims to determine the potential of Bojong village, develop the agro-tourism potential of Bojong village, and develop peeled young coconuts to help make the village's agro-tourism potential a success. This is expected to be able to increase the existence of villages and coconuts typical of Bojong village, so that the people can live more prosperously.